2003
DOI: 10.1046/j.1399-0012.2003.00107.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A monitoring by 2‐h levels: preliminary target levels in stable pediatric kidney transplant recipients

Abstract: Clinical trials in adults have shown that management of transplanted patients with cyclosporin A (CsA) 2-h levels (C2) lead to superior outcome compared with monitoring of 12-h trough levels (C0). In both adults and children, C2 levels enabled a better estimation of the area under the curve concentration than C0 levels. Therefore, it can be suspected that C2 monitoring might also lead to a better outcome in children. Until now C2 target levels for children have not been defined. We measured C2 levels in 101 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…The mean C 2 value that we detected in the renal transplant patients was somewhat lower than the value of 750 μg/l defined as optimal in stable patients by Pape et al [24,25]; however, the large majority of this cohort of children studied received transplants over 5 years ago, prior to the widespread change to the use of tacrolimus as the calcineurin inhibitor of first choice in the UK [26]. All have very stable graft function, and, in a number of instances, ciclosporin levels were intentionally being run at a lower level as a strategy to help prevent ongoing chronic allograft nephropathy.…”
Section: Discussioncontrasting
confidence: 91%
“…The mean C 2 value that we detected in the renal transplant patients was somewhat lower than the value of 750 μg/l defined as optimal in stable patients by Pape et al [24,25]; however, the large majority of this cohort of children studied received transplants over 5 years ago, prior to the widespread change to the use of tacrolimus as the calcineurin inhibitor of first choice in the UK [26]. All have very stable graft function, and, in a number of instances, ciclosporin levels were intentionally being run at a lower level as a strategy to help prevent ongoing chronic allograft nephropathy.…”
Section: Discussioncontrasting
confidence: 91%
“…10,14,36,37 Recent clinical studies in pediatric liver and kidney transplant patients identified a reduced number of rejection episodes if CsA doses were adjusted on the basis of C2 level rather than C0 level monitoring, l with blood level Ͻ500 ng/ml leading to an increased number of acute rejections in one study. 39 On the other hand, monitoring of the C2 level may help to avoid higher serum levels and thereby prevent additional toxic effects such as neuro-and nephrotoxicity. 36 Nevertheless, in some studies-mostly of liver transplant patients-no statistical differences were found with additional C2 monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…In our hands, C2 monitoring was a safe and beneficial method with a lower intra-individual variation of C2 blood levels that can routinely be used in an outpatient clinic. Based on a narrow window of C2 target levels [23], C2 monitoring might detect those patients who had previously been overexposed to CsA although C0 levels were in the therapeutic range. It might therefore also be used in addition to routine C0 monitoring to identify patients who are overexposed to CsA in centers that prefer not to change to routine C2 monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no trials have been performed in children using C2 monitoring for assessment of CsA immunosuppression and it remains unclear if C2 monitoring is superior to trough level monitoring in children [21,22]. Our group defined a C2 target level of 750 ng/ml in stable pediatric transplant recipients by evaluating the 6-month graft function according to C2 levels [23].…”
Section: Introductionmentioning
confidence: 99%